2010
DOI: 10.1002/ppul.21364
|View full text |Cite
|
Sign up to set email alerts
|

Resource usage in outpatient care and reimbursement for cystic fibrosis in Germany

Abstract: International audienceObjective Objective of this study is to assess and evaluate resource use in outpatient treatment in Germany and to compare it with remuneration. Methods Outpatient treatment was evaluated in seven different centers for pediatric and adult CF patients. Data was recorded during one representative month in 2006. A micro-costing approach was used to value resource use data. Results For outpatient treatment mean costs (excluding drugs) of 488 € per patient per quarter occurred. Correlation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The cost analysis of six studies was based on individual resource use under routine care [ 8 , 10 , 13 , 14 , 21 , 22 ], while two calculated annual costs from the aggregate perspective [ 17 , 18 ]. Only two studies examined different cost categories for outpatient treatment allowing the estimation of costs for health personnel [ 22 , 23 ]. Comparison of our findings with those of other studies addressing CF outpatient costs is not straightforward as the methodology used, perspective adopted, and health service utilization and organization vary.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cost analysis of six studies was based on individual resource use under routine care [ 8 , 10 , 13 , 14 , 21 , 22 ], while two calculated annual costs from the aggregate perspective [ 17 , 18 ]. Only two studies examined different cost categories for outpatient treatment allowing the estimation of costs for health personnel [ 22 , 23 ]. Comparison of our findings with those of other studies addressing CF outpatient costs is not straightforward as the methodology used, perspective adopted, and health service utilization and organization vary.…”
Section: Discussionmentioning
confidence: 99%
“…Eidt-Koch assessed the total resource use for CF outpatient care including costs for personnel, laboratory examinations, medication, overhead and infrastructure [ 23 ]. In addition, this study compared the evaluated costs with the actual reimbursement according to the official German Remuneration Scheme for Outpatient Care (EBM) and showed that about half of the costs are left to the CF centres suggesting that "alternative reimbursement schemes should be thought of" [ 23 ]. Specifically, Eidt-Koch's study explored determinants of costs by dividing 326 patients in seven CF centres in Germany according to their age, FEV1 values, certain co-morbidities, and bacterial lung colonization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations